Energy intensity of hydrocarbons in liquid and solid states - G. J. Кабо; L. A. Kabo; L. S. Karpushenkava; A. V. Blokhin (Тонкие химические технологии, 2021)
Objectives. The increased use of unmanned aerial vehicles necessitates the search for jet fuels based on hydrocarbon materials with high energy intensity and physical density. The purpose of the work was to analyze the influence of various factors on the mass energy intensity of hydrocarbons. This analysis is required to substantiate the algorithm for locating energy-intensive CnHm structures.Methods. Combustion energy was calculated using additive procedures. The calculations were performed using Microsoft Excel.Results. During the analysis of the mass energy intensity of CnHm hydrocarbons, the m/n ratio was discovered to be the decisive factor for achieving high values of the mass energy intensity of hydrocarbons. The energy intensity decreases when moving from alicyclic to cyclic hydrocarbons, and this decrease is not compensated by the production of strain energy. An additive scheme that allows the molar volume of hydrocarbons to be predicted with sufficient accuracy is proposed for calculating the volumetric enthalpies of combustion.Conclusions. According to the thermodynamic analysis, n-alkanes have the highest mass energy intensities. The technology for extracting n-alkanes from oil fractions is well developed, and a decrease in the hydrogen content in the fuel results in a decrease in the mass energy intensity. It appears improbable that the mass and volumetric energy intensities of hydrocarbons seem will reach their maximum values simultaneously. Hydrocarbons that have a high m/n value, 2, 3, 4, 5, 6-membered rings, and phenyl fragments may have relatively high mass and volumetric energy intensities at the same time.